2017
DOI: 10.3892/ol.2017.5705
|View full text |Cite
|
Sign up to set email alerts
|

FAM53B truncation caused by t(10;19)(q26;q13) chromosome translocation in acute lymphoblastic leukemia

Abstract: RNA-sequencing of the patient's bone marrow detected fusion transcripts in which the coding sequence of the FAM53B gene (from 10q26) was fused to a genomic sequence (from 19q13) that mapped upstream of the SLC7A10 locus. Reverse transcription-polymerase chain reaction together with Sanger sequencing verified the presence of this fusion transcript. The FAM53B fusion transcript is not expected to produce any chimeric protein. However, it may code for a truncated FAM53B protein consisting of the first 302 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In 1985, De Braekeleer and coworkers reported an acute lymphoblastic leukemia carrying a t(10;19)(q26;q13) as the sole cytogenetic change (122). Thirty-two years later, we described the second case of acute lymphoblastic leukemia with t(10;19)(q26;q13) (89). Molecular analysis demonstrated that the coding sequence of the FAM53B gene (family with sequence similarity 53 member B) from 10q26 was fused to a genomic sequence from 19q13 that mapped upstream of the solute carrier family 7 member 10 (SLC7A10).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 83%
See 3 more Smart Citations
“…In 1985, De Braekeleer and coworkers reported an acute lymphoblastic leukemia carrying a t(10;19)(q26;q13) as the sole cytogenetic change (122). Thirty-two years later, we described the second case of acute lymphoblastic leukemia with t(10;19)(q26;q13) (89). Molecular analysis demonstrated that the coding sequence of the FAM53B gene (family with sequence similarity 53 member B) from 10q26 was fused to a genomic sequence from 19q13 that mapped upstream of the solute carrier family 7 member 10 (SLC7A10).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 83%
“…Many chromosome translocations resulting in truncated or fused genes leading to out-of-frame transcripts have been reported only once. These events might turn out to be recurrent if and when the second case, and then the third et cetera, is reported, as for the leukemias with t(8;19)/KAT6A::LEUTX described between 1988 and 1995 and t(11;20)/ZMYND8::RELA between 2013 and 2018 (33,37,38,40,53,67,(89)(90)(91)(92)(93)(94)(118)(119)(120)(121). In 1985, De Braekeleer and coworkers reported an acute lymphoblastic leukemia carrying a t(10;19)(q26;q13) as the sole cytogenetic change (122).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 98%
See 2 more Smart Citations
“…FAM53B is a new vertebrate gene controlling cell proliferation ( Thermes et al, 2006 ). In acute lymphoblastic leukemia (ALL) cells, the FAM53B fusion transcript could code a truncated FAM53B protein, which was considered to be of great biological significance because of its entire conserved domain, even though the mechanism was unclear ( Panagopoulos et al, 2017 ). A four-gene model of MM consisting of FAM53B , KIF21B , WHSC1 , and TMPO could predict the overall survival of MM patients independently, and the expression of FAM53B was downregulated in high-risk patients compared to low-risk patients.…”
Section: Discussionmentioning
confidence: 99%